Effect of Topical Aplication of Gel Aloe Vera Extract on The UVB-Induced Skin Photoaging in Hairless Rats - Izzatul Lailiyah; Sasangka Prasetyawan; Aulanni'am Aulanni'am (The Journal of Pure and Applied Chemistry Research, 2017)
UVB generates the production of Reactive Oxygen Species (ROS) and decrease antioxidants enzymatic excessively. Both of these biological effects caused photo-aging. Excessive ROS production afforded overexpression of AP-1 as a major regulator of photoaging. This paper figured out the potential of Aloe vera extract as topical gel treatment on the UVB-induced skin photo-aging in twenty male wistar hairless rats (Rattus novergicus) divided into 2 groups. First group was induced by UVB and the second was induced by UVB and topical gel extract Aloe vera treatment. Each group was given treatment for 4 weeks. The expression of MDA and SOD were measured with immunohistochemistry. The result showed that the topical gel therapy decreased the MDA expression and increased SOD expression significantly (p < 0.01). The conclusion from this study was Aloe vera extract had potentially as an alternative topical treatment of photoaging.